Subscribers Satisfaction with the Use of Mobile Money to Renew their National Health Insurance Cards in the North East Region of Ghana - Karim, A. J. (University of Ghana, 2022)
Health financing in Ghana has passed through a number of phases ranging from free health care to ‘’cash and carry’’ and then to health insurance. The Ghana National Health Insurance Authority introduced the mobile money renewal service to help address the numerous challenges affecting the scheme. With this service, subscribers could renew and pay premiums of their NHIS cards anywhere with any type of mobile device. The study population consisted of subscribers who have used the service to renew NHIS cards before with a total sample size of 400 respondents. The study revealed that subscribers’ level of satisfaction was generally high. Among the factors that were found to be affecting subscribers from effectively using the service were; poor network, lack of money in wallet, difficult procedure and lack of knowledge. However, the mean values of these factors were generally low indicating that their effect o subscribers’ satisfaction was low. The study also sought to determine the factors that affect subscribers’ satisfaction with the use of mobile money to renew their NHIS cards in the North East Region of Ghana. Multiple regression analysis of the field data backed by relevant literature revealed that factors such as; perceived ease of use, reliability of service, subscribers experience as well as awareness affects subscribers’ satisfaction with the use of the NHIS mobile money renewal service. Apart from perceived ease of use, all other factors had an inverse relationship with subscribers’ satisfaction. The NHIS officials’ perception about the subscribers’ satisfaction also revealed a high level of satisfaction with their reasons being that there is a drastic reduction in the number of subscribers that visits the scheme offices to renew their NHIS cards. According to them, the service has brought them a number of benefits including; reduction in pressure on staff, improvement in revenue mobilization, reduction in the cost of ICT consumables among others. Among the challenges identified were, high illiteracy rate, inadequate funds, fraudulent activities of some mobile money vendors as well as network challenges.
MPhil. Health Services Management
Keywords: Health financing; Ghana; Ghana National Health Insurance Authority